ISO 9001 version 2015 implementation guide - Buritica Macías, Ángela María (Scientia et Technica, 2019)
Companies that require the implementation of the new version of the quality standard ISO 9001: 2015, must go to a quality consultant to make their application, implying costs and more time to meet this objective. Through this implementation guide, organizations are facilitated to apply the requirements without the need of an advisor and adapt it to their needs. A revision was made to the new version and to the previous one where modifications were found to the numerals from 8 to 10 and structurally emphasized in the context of the organization by including the internal and external factors that affect it. This allows to comply with the requirements of the client in a coherent manner, legal and regulatory in order to increase the satisfaction of the same; it also involved the risks as an effect of an uncertainty associated with its context and the objectives of the organization and incorporated them into the requirements of the standard. Finally, the changes with respect to the 2008 year version are presented so that they can be applied in the update to the new version in the companies that require it.